Faecal proteomics as a novel method to study mammalian behaviour and physiology. (8th April 2021) - Tsutaya, Takumi; Mackie, Meaghan; Sawafuji, Rikai; Miyabe‐Nishiwaki, Takako; Olsen, Jesper V.; Cappellini, Enrico
Abstract: Mammalian faeces can be collected noninvasively during field research and provide valuable information on the ecology and evolution of the source individuals. Undigested food remains, genome/metagenome, steroid hormones, and stable isotopes obtained from faecal samples provide evidence on diet, host/symbiont genetics, and physiological status of the individuals. However, proteins in mammalian faeces have hardly been studied, which hinders the molecular investigations into the behaviour and physiology of the source individuals. Here, we apply mass spectrometry‐based proteomics to faecal samples ( n = 10), collected from infant, juvenile, and adult captive Japanese macaques ( Macaca fuscata ), to describe the proteomes of the source individual, of the food it consumed, and its intestinal microbes. The results show that faecal proteomics is a useful method to: (i) investigate dietary changes along with breastfeeding and weaning, (ii) reveal the taxonomic and histological origin of the food items consumed, and (iii) estimate physiological status inside intestinal tracts. These types of insights are difficult or impossible to obtain through other molecular approaches. Most mammalian species are facing extinction risk and there is an urgent need to obtain knowledge on their ecology and evolution for better conservation strategy. The faecal proteomics framework we present here is easily applicable to wild settings and other mammalian species, and provides direct evidence of their behaviour and physiology.